Analysis of Science Education Supervision to Improve the Quality of Student Output - Hidayat, Calsabila Syasre; Mahardika, I Ketut; Rahma, Ayu Sayyidatina; Nazila, Ika Rokhmatun (International Journal of Education, Information Technology, and Others, 2024)
Supervision of science education is an important step to ensure that teachers provide effective learning and in accordance with the science curriculum. Supervision can provide guidance to teachers to achieve educational goals and produce graduates who are recognized by society. This research uses a literature study method to gain an in-depth understanding of science education supervision. The research results show that science education supervision can help identify student needs, increase teacher competence in science, and improve learning evaluation. With effective supervision, it is hoped that the quality of education in the science field can continue to improve and produce quality graduates. The benefit of this research is that it provides a better understanding of the importance of supervision in improving the quality of student learning outcomes in the field of science education.